2011
DOI: 10.3390/ijms12106919
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Compounds and Total Sugar Content in a Nectarine [Prunus persica (L.) Batsch] Progeny

Abstract: Epidemiological studies suggest that consumption of fruit rich in phenolic compounds is associated with health-protective effects due to their antioxidant properties. For these reasons quality evaluation has become an important issue in fruit industry and in breeding programs. Phytochemical traits such as total phenolics, flavonoids, anthocyanins, L-ascorbic acid, sugar content and relative antioxidant capacity (RAC) were analyzed over four years in flesh fruit of an F1 population “Venus” × “Big Top” nectarine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
54
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 32 publications
31
54
3
Order By: Relevance
“…In the group of phenolics, none of the components correlated with each other, indicating that those traits are genetically independent. A positive correlation was obtained between TPC and sugars (r = 0.514 -0.595), which agrees with the results of Abidi et al (2011). The only exception was the absence of the relationship between TPC and glucose content.…”
Section: Myricetin Kaempferol Quercetin Ellagic Acid Chlorogenic Acidsupporting
confidence: 81%
“…In the group of phenolics, none of the components correlated with each other, indicating that those traits are genetically independent. A positive correlation was obtained between TPC and sugars (r = 0.514 -0.595), which agrees with the results of Abidi et al (2011). The only exception was the absence of the relationship between TPC and glucose content.…”
Section: Myricetin Kaempferol Quercetin Ellagic Acid Chlorogenic Acidsupporting
confidence: 81%
“…Moreover, FRUC and SUC values were showed negative significant correlations with TA (r = -0.34 and r = -0.42, at p < 0.01). In contrast to our results, Abidi et al (2011) reported a positive correlation in grapes between sugar content and total anthocyanins. This is likely because fig genotypes with green or brown fruit skin color have higher FRUC, GLUC, and SUC than do genotypes with black fruit skin color (Çalişkan & Polat, 2011).…”
Section: Correlation Analysescontrasting
confidence: 56%
“…'Bursa Siyahı' may be useful in a breeding study as a donor genotype for both high phytochemical levels and excellent fruit quality characters. Phenotypic and heritability calculations in several fruit species showed that the improvement of TA and TP is possible through selective breeding (Connor et al, 2005;Abidi et al, 2011). Therefore, the favorable fruit characters defined by 'Bursa Siyahı' should be useful in hybridization studies.…”
Section: Correlation Analysesmentioning
confidence: 99%
“…The positive correlation between total sugar and total phenolic that was found in our study, was also reported by Abidi et al (2011) for nectarine fruit and by Pirie and Mullins (1977) for berries; that could be explained by the effect of sugars in the control of phenolic biosynthesis. As DeJong (1999) who found that, the appropriate content of sugars in or near the fruit is important for phenolic compounds production during fruit development.…”
Section: Influence Of Environmental Factors On Phytochemical Compoundsupporting
confidence: 73%